G295(P) Normal observations, safe discharge?. (24th May 2017) - Clark, M; Harris, T; Parik, A; Pott, J; Rolland, D
Abstract : Aims: Clinicians working in emergency departments use 'normal observations' as part of the decision making process when discharging children home. This study examined whether Paediatric Early Warning Scores (PEWS) predict unsafe discharge from the emergency department. Unsafe discharge was defined as a child returns within 7 day with the same condition and requires admission to hospital. Methods: Data was prospectively collected during the routine treatment at Royal London Hospital (n=6122). We tested whether a threshold of 0, 1, 2 or 3 predicted a safe discharge from the emergency department. Results: Unsafe discharge rates: Prediction of unsafe discharge: Conclusion: Higher PEWS are associated with an increased rate of unsafe discharges. More importantly, 20% of unsafe discharges had normal observations. Therefore, 'normal obs' may not predict a safe discharge.